Insights into the phylogenetic and molecular evolutionary histories of Fad and Elovl gene families in Actiniaria - Surm, Joachim M. (Ecol Evol, 2018)
The biosynthesis of long‐chain polyunsaturated fatty acids (LC‐PUFAs, ≥ C(20)) is reliant on the action of desaturase and elongase enzymes, which are encoded by the fatty acyl desaturase (Fad) and elongation of very long‐chain fatty acid (Elovl) gene families, respectively. In Metazoa, research investigating the distribution and evolution of these gene families has been restricted largely to Bilateria. Here, we provide insights into the phylogenetic and molecular evolutionary histories of the Fad and Elovl gene families in Cnidaria, the sister phylum to Bilateria. Four model cnidarian genomes and six actiniarian transcriptomes were interrogated. Analysis of the fatty acid composition of a candidate cnidarian species, Actinia tenebrosa, was performed to determine the baseline profile of this species. Phylogenetic analysis revealed lineage‐specific gene duplication in actiniarians for both the Fad and Elovl gene families. Two distinct cnidarian Fad clades clustered with functionally characterized Δ5 and Δ6 proteins from fungal and plant species, respectively. Alternatively, only a single cnidarian Elovl clade clustered with functionally characterized Elovl proteins (Elovl4), while two additional clades were identified, one actiniarian‐specific (Novel ElovlA) and the another cnidarian‐specific (Novel ElovlB). In actiniarians, selection analyses revealed pervasive purifying selection acting on both gene families. However, codons in the Elovl gene family show patterns of nucleotide variation consistent with the action of episodic diversifying selection following gene duplication events. Significantly, these codons may encode amino acid residues that are functionally important for Elovl proteins to target and elongate different precursor fatty acids. In A. tenebrosa, the fatty acid analysis revealed an absence of LC‐PUFAs > C(20) molecules and implies that the Elovl enzymes are not actively contributing to the elongation of these LC‐PUFAs. Overall, this study has revealed that actiniarians possess Fad and Elovl genes required for the biosynthesis of some LC‐PUFAs, and that these genes appear to be distinct from bilaterians.